2015
DOI: 10.1073/pnas.1418014112
|View full text |Cite
|
Sign up to set email alerts
|

Insular neural system controls decision-making in healthy and methamphetamine-treated rats

Abstract: Patients suffering from neuropsychiatric disorders such as substance-related and addictive disorders exhibit altered decisionmaking patterns, which may be associated with their behavioral abnormalities. However, the neuronal mechanisms underlying such impairments are largely unknown. Using a gambling test, we demonstrated that methamphetamine (METH)-treated rats chose a highrisk/high-reward option more frequently and assigned higher value to high returns than control rats, suggestive of changes in decisionmaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…In the present study, bilateral lesions of the AIC may have prevented the retrieval of the subjective incentive value of the different options prior to response selection, leading to alterations in responding in animals that had previously expressed strong preferences between risky and safe options. Such an explanation may also be helpful in elucidating the conflicting data from previous studies using other operationalized versions of the IGT in rodents, in which manipulations of the insula were observed to either increase (Mizoguchi et al ., ) or decrease (Pushparaj et al ., ) risky choice. These studies utilized different behavioural paradigms, but both temporarily silenced the insula, through either pharmacological or chemogenetic methods and importantly, in both examples, either the safe (Pushparaj et al ., ) or risky (Mizoguchi et al ., ) options were selected relatively infrequently at baseline prior to AIC inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, bilateral lesions of the AIC may have prevented the retrieval of the subjective incentive value of the different options prior to response selection, leading to alterations in responding in animals that had previously expressed strong preferences between risky and safe options. Such an explanation may also be helpful in elucidating the conflicting data from previous studies using other operationalized versions of the IGT in rodents, in which manipulations of the insula were observed to either increase (Mizoguchi et al ., ) or decrease (Pushparaj et al ., ) risky choice. These studies utilized different behavioural paradigms, but both temporarily silenced the insula, through either pharmacological or chemogenetic methods and importantly, in both examples, either the safe (Pushparaj et al ., ) or risky (Mizoguchi et al ., ) options were selected relatively infrequently at baseline prior to AIC inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies utilizing different rodent versions of the IGT have further suggested an involvement of the insula in costā€benefit decisionā€making, although the results are equivocal. AIC lesions and inactivations increased choice of smaller more certain rewards in one study (Pushparaj et al ., ), whereas chemogenetic inhibition of the insula increased choice of a highā€risk high reward option, using a maze based task (Mizoguchi et al ., ). However, both of these paradigms utilized relatively extensive training regimes and did not address the potential contribution of the AIC to interā€individual differences in decisionā€making.…”
Section: Introductionmentioning
confidence: 97%
“…Control injections were 0.5% DMSO in saline solution. Of the 22 articles that we found that used systemic administration of CNO in rats (Ferguson et al, 2011, 2013; Anderson et al, 2013; Michaelides et al, 2013; Boender et al, 2014; Bull et al, 2014; Dellā€™Anno et al, 2014; KƤtzel et al, 2014; Robinson et al, 2014; Chang et al, 2015; Gompf et al, 2015; Mizoguchi et al, 2015; Pienaar et al, 2015; Scofield et al, 2015; Yau and McNally, 2015; Grace et al, 2016; Ma et al, 2016; Marchant et al, 2016; Qiu et al, 2016; Sengupta et al, 2016; Wicker and Forcelli, 2016; Wirtshafter and Stratford, 2016), 2 used chronic treatment (e.g., in drinking water) and 11 used doses >1 mg/kg. Of those that used doses of >1 mg/kg, most used doses of 3 mg/kg, but in a few cases doses were as high as 10 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…In this design, it is impossible to separate out the effects of activation of the DREADD from any unexpected effects of CNO, which could be the enhancement or blockade of the expected result of DREADD activation. In terms of dosing, a wide range of doses (0.2ā€“10 mg/kg) is regularly used in DREADD experiments (Alexander et al, 2009; Ferguson et al, 2011, 2013; Ray et al, 2011; Agulhon et al, 2013; Anderson et al, 2013; Farrell et al, 2013; Michaelides et al, 2013; Wang et al, 2013; Boender et al, 2014; Bull et al, 2014; Dellā€™Anno et al, 2014; KƤtzel et al, 2014; Robinson et al, 2014; Zhu et al, 2014; Chang et al, 2015; Gompf et al, 2015; Mizoguchi et al, 2015; Pienaar et al, 2015; Scofield et al, 2015; Yau and McNally, 2015; Grace et al, 2016; Ma et al, 2016; Marchant et al, 2016; Qiu et al, 2016; Sengupta et al, 2016; Wicker and Forcelli, 2016), and there is seldom any explanation given as to how the dose that was used was decided upon. Using the lowest effectual dose in the assay to be performed, that which in the non-DREADD-expressing animals is experimentally silent, would seem the most straightforward way to minimize any off-target effects of CNO.…”
Section: Relevance To the Dreadd System: Is Cno An Inert Ligand?mentioning
confidence: 99%
“…Both of these studies employed DREADDs to support the notion that MSNs in thee D1 direct-pathway, and D2 indirect-pathway, play a crucial role in activating, and inhibiting, reward-related locomotor activation. Also related to the influence of psychostimulants on neuronal function, Mizoguchi et al (Mizoguchi et al, 2015) found using hM4Di and hM3Dq DREADDs that risky behavior in a rat gambling task involved insular cortex, as does methamphetamine-induced increases in risky behavior.…”
Section: Section 2 ā€“ Highlights Of Dreadd Applications In Behavioral mentioning
confidence: 99%